Effects of Dopants in PtSn/M‐Silicalite‐1 on Structural Property and on Catalytic Propane Dehydrogenation Performance. Issue 14 (8th April 2020) - Zhou, Shuai; Liu, Shuangfei; Jing, Fangli; Jiang, Changzhou; Shen, Jun; Pang, Yanping; Luo, Shizhong; Chu, Wei
Abstract: The various metal‐doped Silicalite‐1 (M−S1, M=Mg, Al, Fe and In) supports were prepared by hydrothermal synthesis method, then were used to disperse the PtSn species through impregnation. The resulting solids were further characterized through XRD, N2 adsorption/desorption isotherms, XPS, H2 ‐TPR, NH3 ‐TPD, Raman spectroscopy and TG techniques to investigate the structural property before and after propane dehydrogenation reaction. The results exhibited that the introduction of various metal dopants had profound effects on pore structure, reducibility, acidity and surface content of Pt which was directly related to the activation of propane. And the surface content of Pt acted as the dominant role for converting propane. As a consequence, the maximum initial conversion of propane was obtained over Fe‐modified PtSn/Fe−S1 sample, but it deactivated fast as well because of the coke deposition. Abstract : The catalytic activity of propane dehydrogenation showed evident dependence on surface Pt content which was significantly affected by the promoters.